Cities and the structure of social interactions: Evidence from mobile phone data - Konstantin Büchel; Maximilian von Ehrlich-Treuenstätt (University of Bern, Department of Economics, 2016)
Social interactions are considered pivotal to urban agglomeration forces. This study employs a unique dataset on mobile phone calls to examine how social interactions differ across cities and peripheral areas. We first show that geographical distance is highly detrimental to interpersonal exchange. We then reveal that individuals residing in high-density locations do not benefit from larger social networks, but from a more efficient structure in terms of higher matching quality and lower clustering. These results are derived from two complementary approaches: Based on a link Formation model, we examine how geographical distance, network overlap, and sociodemographic (dis)similarities impact the likelihood that two agents interact. We further decompose the effects from individual, location, and time specific determinants on micro-level network measures by exploiting information on mobile phone users who change their place of residence.
Keywords: R1; R23; Z13; D85; 330; Social Interactions; Agglomeration Externalities; Network Analysis; Sorting